Meningkatkan Hasil Belajar Pak Siswa Kelas IV Secara Mandiri Melalui Pemberian Reward Dengan Model Problem Based Learning - Masliana Tarigan; Dicky Aprianto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to determine how the learning process is based on practical learning after giving reward with the Problem Based Learning (PBL) model. This Classroom Action Reserch has 4 stages, namely planning, implementation, evaluation and reflection. The subjects in this study were 12 fourth grade students, namely 3 males and 9 females. Data collection used in this study is 1. Test technique with the target achievement of mature, proficient, feasible, and newly developing2. Observation with the Pancasila Student Profile indicator with self-direction and mutual cooperation the result of the study show that the determination of the PBL model can improve learning outcomes where in Cycle 1 wich was included in the low category increased to 37% feasible, proficient 50%, Proficient 13%. And in cycle 2 it increased to proficient 37% and proficient 63%.